2010
DOI: 10.1590/s1676-06032010000300033
|View full text |Cite
|
Sign up to set email alerts
|

Serpentes do Município de Viçosa, Mata Atlântica do Sudeste do Brasil

Abstract: Apresentamos aqui, com base em exemplares depositados em coleções científicas, uma lista das espécies de serpentes do Município de Viçosa, localizado em uma porção da Mata Atlântica do Estado de Minas Gerais, Sudeste do Brasil. Trinta e quatro espécies foram confirmadas em Viçosa. Outras duas possuem registros duvidosos e cinco espécies que foram registradas em municípios vizinhos poderiam também ocorrer em Viçosa. Informações sobre distribuição e história natural das serpentes são apresentadas, baseadas em da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 71 publications
2
17
1
4
Order By: Relevance
“…The similarity dendrogram (cophenetic correlation coefficient = 0.9088) (Figure 2) showed that the reptile fauna of Juiz de Fora is more similar to the region of Viçosa (Costa et al 2009(Costa et al , 2010. These two locations have in common 30 species, and in contrast, 41 different species, which helps to confirm the high diversity between the regions of the state of Minas Gerais, which provides a high gamma diversity for the state as a whole.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…The similarity dendrogram (cophenetic correlation coefficient = 0.9088) (Figure 2) showed that the reptile fauna of Juiz de Fora is more similar to the region of Viçosa (Costa et al 2009(Costa et al , 2010. These two locations have in common 30 species, and in contrast, 41 different species, which helps to confirm the high diversity between the regions of the state of Minas Gerais, which provides a high gamma diversity for the state as a whole.…”
Section: Resultsmentioning
confidence: 80%
“…Another fact that must be taken into consideration is the time of operation of the CHUFJF-Reptile collection (active since 2000), making this collection much more recent than that of the João Moojen Zoology Museum (in operation since 1933) in Viçosa, for example. The latter is an important source of information on regional diversity, since the region is under represented in other Brazilian reference collections (Costa et al 2010), such as the herpetological collections of the National Museum of Rio de Janeiro Federal University and the Zoology Museum of the University of São Paulo, which are the largest collections of reptiles in the Neotropical Region Ernst & Barbour (1989), Argôlo & Freitas (2002), Souza et al (2003), Souza (2004), Novelli & Sousa (2007) Phrynops geoffroanus (Schweigger, 1812) Lakes, ponds, streams and rivers and disturbed environments, such as reservoirs Colombian Amazon to the state of Rio Grande do Sul, and also parts of Uruguay and northern Argentina Ernst & Barbour (1989), Lema & Ferreira (1990) (South America and Central America). These facts demonstrate the importance of regional collections, and highlight how the reptilian fauna of the CHUFJF-Reptiles can be representative of local, regional and even national levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A primeira tem na Serra do Brigadeiro o segundo registro para o estado de Minas Gerais (Costa et al 2010), além do limite leste de sua distribuição (Figura 12a). Embora a localidade tipo desta espécie seja o estado da Bahia, a mesma é dada como incerta (Di-Bernardo 1992).…”
Section: ) O Lagartounclassified
“…Com relação aos répteis, também se constatou elevada riqueza quando comparada a estudos realizados em localidades próximas. Assis (1999) Silveira et al (2010) reportam 58 espécies de serpentes para a região de Ouro Preto, Mariana e Itabirito, e Costa et al (2010) que registraram 34 espécies de serpentes para o município de Viçosa. Do total de espécies de serpentes registradas por Costa et al (2010), 12 não foram registradas na Serra do Brigadeiro, localizada a aproximadamente 35 km do município de Viçosa.…”
Section: Considerações Finaisunclassified